2018
DOI: 10.3390/w10040531
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Ecosystem Services in Mining Regions: Modelling Options for Policy Development Support

Abstract: The ecosystem services (ES) approach offers an integrated perspective of social-ecological systems, suitable for holistic assessments of mining impacts. Yet for ES models to be policy-relevant, methodological consensus in mining contexts is needed. We review articles assessing ES in mining areas focusing on freshwater components and policy support potential. Twenty-six articles were analysed concerning (i) methodological complexity (data types, number of parameters, processes and ecosystem-human integration le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 130 publications
(334 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, the degree of mining's impacts on aquatic habitats and freshwater ecosystem services vary at each lifecycle stage of mining, raising multiple sustainability concerns [68]. While we confirmed that physicochemical quality is preserved in the mining-recharged headwaters, questions arise regarding how much of the anthropogenic impact on the Mashcon watershed is attributable to mining development.…”
Section: Systemic Challengesmentioning
confidence: 54%
See 2 more Smart Citations
“…Furthermore, the degree of mining's impacts on aquatic habitats and freshwater ecosystem services vary at each lifecycle stage of mining, raising multiple sustainability concerns [68]. While we confirmed that physicochemical quality is preserved in the mining-recharged headwaters, questions arise regarding how much of the anthropogenic impact on the Mashcon watershed is attributable to mining development.…”
Section: Systemic Challengesmentioning
confidence: 54%
“…A reduced soil quality in turn is also adverse for vegetation. The overall reduction of the ecosystem state causes a decline in ecosystem service production, such as the impaired mediation of mass and liquid flows or lower availability of plants and animals for non-mining stakeholders [68].…”
Section: Systemic Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple pressures threaten European stream ecosystems [1][2][3][4]. These pressures result from various human activities, such as modifications of river morphology [5][6][7] and hydrology [6,8,9], intensive agriculture [10][11][12][13][14], urbanization [13,15,16] and mining [17][18][19]. Together, these activities often lead to the degradation of stream ecosystems, reducing biodiversity, water security and ecosystem services [4,20].…”
Section: Introductionmentioning
confidence: 99%
“…The methods of collecting, preserving and analysing water samples should be performed using the standardised procedure. However, it should be noted that the physical and chemical characteristics of water can have high temporal variability [29,30]. That is, measurements can be highly variable within a day, month, season, and year.…”
Section: Physical-chemical Monitoringmentioning
confidence: 99%